2003
DOI: 10.1084/jem.20021859
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Production of CCL17 In Vivo

Abstract: Dendritic cells (DCs)* fulfill an important regulatory function at the interface of the innate and adaptive immune system. The thymus and activation-regulated chemokine (TARC/CCL17) is produced by DCs and facilitates the attraction of activated T cells. Using a fluorescence-based in vivo reporter system, we show that CCL17 expression in mice is found in activated Langerhans cells and mature DCs located in various lymphoid and nonlymphoid organs, and is up-regulated after stimulation with Toll-like receptor lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 61 publications
6
107
1
Order By: Relevance
“…In contrast, injection of Gallium nitrate, known to delay graft rejection, resulted in a significantly prolonged persistence of heart action in CCR4-deficient mice compared to wild type controls . These results could be confirmed by findings in CCL17-deficient mice, CCL17 being the specific ligand of CCR4 [Alferink et al, 2003]. Besides constitutively expressed chemokines like CCL19 and CCL21 that mainly recruit naive T cells in the lymph node, inflammatory chemokines like CCL2, CCL3, CCL17 and CCL22 mainly cause accumulation of activated T cells and T memory cells in inflamed organs.…”
Section: Potential Of Heterotopic Cardiac Transplantation In Mice As supporting
confidence: 75%
“…In contrast, injection of Gallium nitrate, known to delay graft rejection, resulted in a significantly prolonged persistence of heart action in CCR4-deficient mice compared to wild type controls . These results could be confirmed by findings in CCL17-deficient mice, CCL17 being the specific ligand of CCR4 [Alferink et al, 2003]. Besides constitutively expressed chemokines like CCL19 and CCL21 that mainly recruit naive T cells in the lymph node, inflammatory chemokines like CCL2, CCL3, CCL17 and CCL22 mainly cause accumulation of activated T cells and T memory cells in inflamed organs.…”
Section: Potential Of Heterotopic Cardiac Transplantation In Mice As supporting
confidence: 75%
“…4A). Although previous studies indicated that DCs and macrophages are potent sources of these chemokines 16, 17 , Ccl17 and Ccl22 expression was much higher in the pLN T cell fraction than in the non-T cell compartment, which may include B cells, macrophages, mast cells, NK cells, and DCs (Fig. 4A).…”
Section: Resultsmentioning
confidence: 77%
“…This receptor has also been identified on monocytes, Langerhans DC cells, monocytes, NK cells, and platelets. Alferink and colleagues demonstrated a significant prolongation of cardiac allograft survival when fully mismatch hearts were transplanted into immunosuppressed CCL17−/− recipients 81. Follow-up studies by Huser and associates using CCR4−/− recipient mice also demonstrated prolonged cardiac allograft survival and even more profound effects with the addition of gallium nitrate 82.…”
Section: Chemokine-cc Chemokine Receptormentioning
confidence: 98%
“…CCR7 and its ligands CCL19 and CCL21 play a role, in part, in the localization of antigen loaded DC and antigen specific T cells within T cell rich zones, which are critical for the initiation of an adaptive immune response 81, 85. CCR7 is expressed on naïve and memory T lymphocytes, on a subset of activated T cells within secondary lymphoid organs, and on mature DC and B cells 86.…”
Section: Chemokine-cc Chemokine Receptormentioning
confidence: 99%